Analysis of system with variable parameters, invariant to additive interference - Dolinskiy, Rostislav (Eastern-European Journal of Enterprise Technologies, 2015)
The analysis ofphase-differencemodulationfeaturesincaseofdefinedtypeoftransmissionsystemandnoisetypewas performed. Interference resistance comparison analysis was carried out for systems, which use phase-difference modulation, regarding additive interference, in condition when system<s>s</s> parameters are variable. As systems which use phase difference modulation of different orders should use corresponding communication systems with constant or variable parameters, such systems are investigated. The research of invariance of the system with variable parameters to additive interference, shaped as harmonic fluctuation with random amplitude, frequency and phase was conducted. Logicalschemeof complex signalsreceiver ofphase-differencemodulated signals, which are divided into data flows, which are processed in parallel was reviewed. Implementation of phase difference modulation in modern communication systems can bring great benefits for radio networks, which is used for communication with mobile customer terminals. Depending on which interference types are common to the radio network, difference modulation implementation will provide invariance to them, so systems with variable or constant parameters, which use corresponding phase-shift modulation order should be used.The conclusion was made related to the interference resistance of phase-difference modulated signals, in the case of signal characteristics are prior known and change linearly. Usage of phase-difference modulation would grant immunity to the Doppler effect, and focused interference, and this will allow to increase the signal interference immunity for mobile terminals. Received results should be used for further development of modern communication systems, which use orthogonal frequency division multiplexing